2020
DOI: 10.1101/2020.09.16.300525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A neural and behavioral tradeoff underlies exploratory decisions in normative anxiety

Abstract: Exploration reduces uncertainty about the environment and improves the quality of future decisions, but at the cost of uncertain and suboptimal outcomes. Although anxiety increases intolerance to uncertainty, it remains unclear whether and how anxiety modulates exploratory decision-making. We use a three-armed-bandit task in both loss and gain domains and find that higher trait-anxiety increases exploration, which in turn underlies an inverse-U-shaped relationship between anxiety and overall performance. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 104 publications
2
4
0
Order By: Relevance
“…According to our factor structure, STAI-T primarily reflects the Negative Affect factor, which was associated with an increase in directed exploration in Experiment 1. This finding matches the recent work by Aberg et al (2021). However, this relationship disappeared in Experiment 2 when the reward prediction task was added, implying that the effect of Negative Affect might not be robust to task modification.…”
Section: Tablesupporting
confidence: 91%
See 1 more Smart Citation
“…According to our factor structure, STAI-T primarily reflects the Negative Affect factor, which was associated with an increase in directed exploration in Experiment 1. This finding matches the recent work by Aberg et al (2021). However, this relationship disappeared in Experiment 2 when the reward prediction task was added, implying that the effect of Negative Affect might not be robust to task modification.…”
Section: Tablesupporting
confidence: 91%
“…On one hand, people with anxiety symptoms tend to avoid uncertain options (Charpentier et al, 2017), which reduces exploration. On the other hand, anxiety is associated with the elevated valuation of information (Aberg et al, 2021;Bennett et al, 2021), which encourages exploration behavior to reduce uncertainty. It is also possible that the apparently increased exploration reflects an overall tendency to behave more randomly (Aylward et al, 2019).…”
Section: Underestimation Of Uncertaintymentioning
confidence: 99%
“…Although we find a negative relationship between symptoms and directed exploration, our findings linking elevated symptoms to greater ambiguity aversion share some similarity to the greater exploration in depression (25) and trait anxiety (24) observed in previous work.…”
Section: Discussionsupporting
confidence: 88%
“…Faster learning rates were also associated with more severe psychotic symptoms. Another recent study in healthy participants showed that normative levels of trait anxiety were positively associated with exploratory behavior and that an inverted-U pattern characterized performance differences; namely, moderate anxiety and associated levels of exploration led to higher levels of performance than those with very high anxiety or very low anxiety (i.e., who explored too much or too little; (24)). This finding was in the context of a volatile environment with changing reward or loss probabilities and appeared to be driven by reduced reward-seeking behavior and an elevated drive to reduce uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies in AI have only very recently begun to examine differences in preference precision (and hence informationseeking; see (Smith, Schwartenbeck, et al, 2020;Smith, Taylor, Stewart, et al, 2021)). However, work on exploratory drives within expanded RL models has suggested altered patterns of information-seeking in depression, anxiety, and other psychiatric disorders (Aberg et al, 2022;Fan et al, 2021;Smith, Taylor, Wilson, et al, 2021;Waltz et al, 2020). Whether and how information-seeking drives relate to SWB has not been empirically assessed (for some interesting Smith,Varshney,Nagayama,Kazama,Kitagawa,Managi,& Ishikawa www.internationaljournalofwellbeing.org 14 recent theoretical discussion, see (Miller et al, 2022)).…”
Section: Information-seeking and Sensitivity To Uncertaintymentioning
confidence: 99%